Inhibitory effects of oil palm leaf extract on osteoclastogenesis in RAW 264.7 macrophages - Safa, Parastoo; Ismail, Patimah; Md Noor, Sabariah; Abd Manan, Nizar (Hibiscus Publisher, 2024)
Osteoporosis is a bone disorder caused by an imbalance in the bone remodelling process, specifically between osteoblastogenesis and osteoclastogenesis, and is associated with increased oxidative stress. This study aims to investigate the antioxidant activity of oil palm leaf extracts (OPLEs) and their effects on osteoclastogenesis in murine macrophages (RAW 264.7), comparing the results with those of vitamin C (VC). Methanol extract of oil palm leaves (MEOPL) demonstrated the highest total phenolic content (TPC) at 284.26 mg GAE/g dry weight. The antioxidant activity, assessed via DPPH scavenging and FRAP assays, showed that MEOPL had a DPPH inhibition rate of 89.41% and a FRAP value of 105.67%. In cytotoxicity assays, MEOPL-treated cells exhibited significantly higher viability compared to VC-treated cells, with viability percentages exceeding 60% at concentrations up to 0.625 mg/mL. MEOPL also significantly reduced osteoclastogenesis, as indicated by a dose-dependent decrease in TRAP-positive multinucleated cells and a notable reduction in RANKL gene expression. These findings suggest that MEOPL possesses superior anti-osteoclastogenic properties compared to VC and holds promise as a potential therapeutic agent for the prevention and treatment of osteoporosis. However, as this study utilised an in vitro model, the direct translation of these results to clinical scenarios is limited, and further in vivo studies are necessary to confirm the clinical relevance of MEOPL.